Implementatation of Religious Moderation in the Constitution and College : The Effectiveness of Socialization of the FSEI IAIN Constitutional Law Study Program in the 4.0 Era - Syah, Mabrur; Agustian, Tomi; Habiburrahman, Habiburrahman; Sari, Windi Puspitas (NEGREI: Academic Journal of Law and Governance, 2023)
Religious moderation is actually the key to creating tolerance and harmony, both at the local and national levels. Religious moderation should be understood as a balanced, non-exclusive, and tolerant religious attitude.  In the midst of the strengthening of radical understanding among the younger generation, it is necessary to convey a narrative about Islam that is cool, tolerant and non-violent among students and university students. This study aims to find out (1) the Socialization Strategy of the Constitutional Law Study. The method used in Research is qualitative research. From the studies carried out it is known; First;  The socialization strategy of the FSEI IAIN Curup Constitutional Law Study Program on Religious Moderation in the 4.0 era is to socialize to the community in collaboration with the Indonesian Ulema Council (MUI) of Rejang Lebong Regency by campaigning for the importance of Washatiyyah/moderate Islamic views for the plural Republic of Indonesia, through social media, (Fb, IG, Twitter, and YouTube). Second, the Effectiveness of the Introduction of the FSEI IAIN Constitutional Law Study Program Curup based on religious moderation in the 4.0 era is quite good with the increasing interest of prospective new students studying in the Constitutional Law study program, and the campaign about the importance of Washatiyyah/moderate Islamic views for the plural Republic of Indonesia is increasingly spread among students of the Constitutional Law Study Program through Social Media portals.